Methodological guidelines for a rapid appraisal of agricultural innovation systems under agroecology (RAAIS-AE) - Ouerghemmi, Hassen; Frija, Aymen; Shiri, Zahra; Rejeb, Hichem (Frontiers Media SA, 2024)
The agricultural innovation system (AIS) is an approach that considers agricultural innovation from a multidisciplinary perspective. The Rapid Appraisal of Agricultural Innovation Systems is one of the commonly used operational methods. It involves a series of structured and participatory activities, including interviews, focus group discussions, and stakeholder workshops, to identify the actors, institutions, and relationships involved in the AIS, as well as the strengths and weaknesses of the system. This approach has been structured in such a manner that it adapts easily to different contexts where different stakeholders, such as developers, academicians, and policymakers are working with community members on innovation. A reflection on the concept -what to know (the requirements) and what to get (the outputs) is necessary for coming up with practical, reflective analysis and applicable procedures for a deeper understanding of the context where the innovations are introduced. Following this will enable us to fully understand the bottlenecks in transitioning from conventional systems to an agroecological model thus pinpointing potential entry points for promoting these systems’ dissemination and scaling.